2021
DOI: 10.18632/aging.203456
|View full text |Cite
|
Sign up to set email alerts
|

m6A regulator-mediated methylation modification patterns and tumor microenvironment infiltration characterization in hepatocellular carcinoma

Abstract: Background: There is increasing evidence of the epigenetic regulation of the immune response in cancer. However, the specific functions and mechanisms of RNA N6-methyladenosine (m6A) modification in the cell infiltration in the hepatocellular carcinoma (HCC) tumor microenvironment (TME) is unknown. Methods: We systematically analyzed the m6A-modification patterns of 371 HCC samples based on 23 m6A regulators, and determined their correlation with TME cell-infiltrating characteristics. Principal-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…ese processes help to protect tumor cells from clearance, inhibit cell death, and promote proliferation to further aid tumor cell migration and metastasis. Most of the current studies have focused on immunomodulation of tumors [28], focusing on addressing the sustained suppression of adaptive immune responses by TME [29]. Encouragingly, previous studies have demonstrated a strong association between m 6 A methylation and tumor immunotherapy; for example, studies have reported a broad regulatory mechanism of m 6 A on the tumor microenvironment in gastric cancer [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese processes help to protect tumor cells from clearance, inhibit cell death, and promote proliferation to further aid tumor cell migration and metastasis. Most of the current studies have focused on immunomodulation of tumors [28], focusing on addressing the sustained suppression of adaptive immune responses by TME [29]. Encouragingly, previous studies have demonstrated a strong association between m 6 A methylation and tumor immunotherapy; for example, studies have reported a broad regulatory mechanism of m 6 A on the tumor microenvironment in gastric cancer [25].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of previous studies on TME may be that they have focused on trends in only a few immune cells. For example, baseline levels of CD4+/CD8+ T cells, macrophage M1, and NK cells, and baseline levels of inflammatory cytokines in tumor invasion have been associated with immune responses [29][30][31]. In contrast, most studies targeting m 6 A modulators in TME have also focused on a single TME cell type (macrophages and CD8 T cells) or a single m 6 A modulator, which has led to the characterization of TME immune cell infiltration mediated by the combined effects of multiple m 6 A modulators not being adequately studied [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, m6A modification is greatly affected by the expression and function of these regulatory proteins, and studying these regulatory proteins can enhance understanding of the role of m6A in gene regulation ( Chong et al, 2021 ). It has also been observed that m6A modification under the influence of regulatory factors is associated with inflammation, the tumor microenvironment (TME), and immune response ( Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The immune-desert and immune-excluded phenotypes can be considered as non-in ammatory tumors, with little or no immune cell in ltration in the TME. The immunein ammatory phenotype was known as a thermo tumor and was characterized by extensive immune cell in ltrates in the TME [32][33][34][35]. Although a large number of immune cells also existed in the immuneexcluded phenotype, they only existed in the stroma around the tumor cell nest and failed to break through the tumor matrix to kill tumor cells or inhibit tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%